Design Training Kit STM32F1 ARM Cortex on Microprocessor and Microcontroller System - Akbar, Junaidi; Suyitno, Amin; Dethan, Jacob Febryadi Nithanel (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Along with the plan of the Electrical Engineering study program for laboratory development, especially the control system laboratory, the teaching team also prepares itself to make a laboratory development plan by multiplying practicum modules accompanied by training kits. To answer these problems, one of them is conducting laboratory-based research. The research conducted in the form of design of STM32F1 ARM Cortex training kit is used to learn the basic knowledge of using microprocessor and microcontroller system applications with its implementation in the form of I/O (Input/Output), LCD Interface (Liquid Crystal Display), HC-SR04 sensor to measure and detect an object, DHT11 Sensor to measure temperature, humidity and Thermostat, ADC (Analog Digital Converter) 12 Bit, PWM (Pulse Width Modulation) on Duty Cycle, RTC (Real Time Clock) for Digital Clock and Alarm. The results showed that the C/C++ program created using the STM32CubeIDE application for implementation consisting of 10 experiments ran successfully on the microprocessor and microcontroller system. So that the STM32F1 ARM Cortex Training Kit can be used in learning microprocessor and microcontroller system practicum.